FOOD OF TWO SIZE-GROUPS OF THE CATFISH MYSTUS GULlO (HAMILTON-BUCHANAN) IN VEMBLAI CANAL, VYPEEN ISLAND - Ritakumari, S. D.; Ajitha, B. S.; Balasubramanian, N. K. (Journal of Indian Fisheries Association, 2006)
The stomach contents of two length-groups of the catfish Mystus gulio collected from Vemblai Canal in Vypeen Island (Kochi) were examined by frequency of occurrence and points methods. Analyses using standard indicesÂ proved difference in diet composition between the two size-groups. Keywords: Diet analysis, prey diversity, dietary breadth